Seroprevalence of small ruminant caprine arthritis encephalitis lentivirus among goats from selected small ruminant farms in Selangor, Malaysia - Abdullah, Faez Firdaus Jesse; Bitrus, Asinamai Athliamai; Abba, Yusuf; Raju, Veenosha Nehru; Hambali, Idris Umar; Peter, Innocent Damudu; Haron, Abd Wahid; Mohd Lila, Mohd Azmi; Mohd Norsidin, Jefri (Veterinary World, 2018)
Background and Aim: Caprine arthritis encephalitis (CAE) is an important viral disease of small ruminants particularly in dairy goats with severe social and economic implication. Hence, this study was designed to determine the seroprevalence of CAE virus (CAEV) among goat population in selected small ruminant farms in Selangor and the risk factors associated with the occurrence of the disease. Materials and Methods: Blood samples were collected from a total of 91 goats selected at random. Blood serum was harvested and used for competitive enzyme-linked immunosorbent assay test to detect antibodies against CAE virus. Results: The result obtained showed that 8/91 (8.8%) of the goats were seropositive for CAEV. In addition, biosecurity management, source of origin and sex of the animal were observed to be important risk factors associated with the occurrence of CAE in goats. Conclusion: The findings of this study affirmed that the seroprevalence of CAEV infection among goat population in small ruminant farms in Selangor, Malaysia, is low. However, there is need to institute strict control measures such as testing and culling positive animals or separation of infected animals from those that tested negative to the disease for effective eradication of the disease.